Suspended Sediment Analysis of Changes in Mangrove Forest Area Using Sentinel-2 Imagery at Citarum River Estuary, Muara Gembong District, Bekasi Regency - Zakiyah, Umi; Tricahyo, R. Bagas; Rusydi, Alfi Nur Rusydi (Faculty of Fisheries and Marine, Universitas Riau, 2025)
This study investigates the distribution of suspended sediments and the dynamics of mangrove forest areas in the Citarum River Estuary, Muara Gembong District, Bekasi Regency, over three observation periods: 2018, 2021, and 2024. The research employs a survey method with an associative approach. Suspended sediment samples were collected using a simple random sampling technique at eight designated locations within the estuary. The analysis of suspended sediment distribution utilized Sentinel-2A satellite imagery, with the Wirasatriya algorithm identified as the most effective for this purpose. The findings indicate an increase in the total area of suspended sediments over time, measuring 1,134.92 hectares in 2018, 1,244.74 hectares in 2021, and 1,254.38 hectares in 2024. Additionally, there was a notable shift in sediment concentration patterns, with low-concentration sediments (63.19%) dominating in 2018, while medium concentrations (100–220 mg/L) became more prevalent in 2021 (43.90%) and 2024 (47.65%). Mangrove forest areas were classified using a supervised classification method integrated with the random forest algorithm. The results revealed a continuous increase in mangrove forest cover during the study period, with a 20.01% expansion between 2018 and 2021, followed by an additional 30.65% growth from 2021 to 2024. Correlation analysis demonstrated a strong association between suspended sediment distribution and changes in mangrove forest area, with a correlation coefficient of 0.814 and a determination coefficient of 0.662. These findings highlight the interconnected dynamics of sediment distribution and mangrove forest development in the estuarine environment